2021
DOI: 10.1158/1535-7163.mct-21-0083
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Tumor–Stromal IL6/STAT3 Signaling through IL1 Receptor Inhibition in Pancreatic Cancer

Abstract: A hallmark of pancreatic ductal adenocarcinoma (PDAC) is the presence of a dense, desmoplastic stroma and the consequent altered interactions between cancer cells and their surrounding tumor microenvironment (TME) that promote disease progression, metastasis, and chemoresistance. We have previously shown that IL6 secreted from pancreatic stellate cells (PSC) stimulates the activation of STAT3 signaling in tumor cells, an established mechanism of therapeutic resistance in PDAC. We have now identified the tumor … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…Cell suspension of whole pancreas obtained from KPC orthotopic mice (same procedure as described above) underwent magnetic column separation to obtain Ly6G + cells as per mouse Myeloid-Derived Suppressor Cell Isolation Kit manufacture’s protocol (Miltenyi Biotec). Ly6G + cells were then co-cultured with KPC CAFs [9,12] in standard 6-well plates. The conditions of the experiment were: (1) CAFs alone (2×10 5 cells per well); (2) CAFs + intra-tumoral Ly6G + cells (10 6 cells per well)’ (3) CAFs pre-treated with Anakinra (α-IL-1R1 inhibitor; with license from SOBI Pharmaceuticals, Sweden) 50 μg/mL + intra-tumoral Ly6G + cells; and (4) CAFs + intra-tumoral Ly6G + cells treated with anti-IL-1β neutralizing antibody 10 μg/mL (R&D Systems cat# AF-401-NA).…”
Section: Detailed and Supplementary Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell suspension of whole pancreas obtained from KPC orthotopic mice (same procedure as described above) underwent magnetic column separation to obtain Ly6G + cells as per mouse Myeloid-Derived Suppressor Cell Isolation Kit manufacture’s protocol (Miltenyi Biotec). Ly6G + cells were then co-cultured with KPC CAFs [9,12] in standard 6-well plates. The conditions of the experiment were: (1) CAFs alone (2×10 5 cells per well); (2) CAFs + intra-tumoral Ly6G + cells (10 6 cells per well)’ (3) CAFs pre-treated with Anakinra (α-IL-1R1 inhibitor; with license from SOBI Pharmaceuticals, Sweden) 50 μg/mL + intra-tumoral Ly6G + cells; and (4) CAFs + intra-tumoral Ly6G + cells treated with anti-IL-1β neutralizing antibody 10 μg/mL (R&D Systems cat# AF-401-NA).…”
Section: Detailed and Supplementary Methodsmentioning
confidence: 99%
“…Emerging evidence implicates stromal inflammation in the PDAC tumor microenvironment (TME)—predominantly through inflammatory polarization of cancer-associated fibroblasts (iCAF) and CAF-derived secretion of IL-6 [6]—as a major driver of chemoresistance in PDAC [7]. Furthermore, prior work from our group has revealed that CAF-derived IL-6 engages in tumor-permissive crosstalk by activating STAT3 signaling within tumor cells [8], and that heightened CAF-tumor cell IL-6/STAT-3 signaling crosstalk is a central mediator of chemoresistance in PDAC [9]. As such, how tumor-permissive inflammatory cues such as neutrophil-lymphocyte balance intersect with such signaling mechanisms underlying therapeutic resistance in PDAC remains critically underexplored.…”
Section: Introductionmentioning
confidence: 99%
“…The tumor stroma, as a critical component of the TME, actively contributes to cancer proliferation, angiogenesis, invasion and metastasis, immune evasion, and resistance to cancer therapy (3,4). The function of stromal cells and their interaction with cancer cells within the TME are modulated by expression and secretion of various signaling molecules such as growth factors (5)(6)(7), chemokines (8)(9)(10), cytokines (11)(12)(13)(14), and proteolytic enzymes (15)(16)(17). Although once thought to be limited to the degradation of ECM, the role of proteases in tumors is now better understood to be significantly more complicated and critical.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond stromal desmoplasia and the biomechanical properties of extracellular matrix (ECM) components that impede drug delivery and T-cell infiltration ( 8 ), emerging evidence implicates functional heterogeneity in the cancer-associated fibroblast (CAF) compartment as a key stromal-mediated mechanism of immunotherapy resistance in PDAC ( 9, 10 ). In particular, IL1-mediated polarization of CAFs toward a secretory phenotype, characterized by elaboration of IL-6, CXCL1, CXCL12, and LIF ( 11, 12 ), propagates pro-inflammatory tumor-stromal-immune crosstalk in the PDAC TME that drives therapeutic resistance ( 13 ). These tumor-permissive inflammatory CAFs (iCAF)—which co-exist in a dynamic equilibrium with other functionally divergent CAF sub-populations such as myofibroblastic CAFs (myCAFs) and antigen-presenting CAFs (apCAFs) ( 14, 15 )—beckon immunosuppressive TAMs and MDSCs to the TME, dampen anti-tumor adaptive immunity, and promote immune evasion in PDAC ( 11, 13, 16, 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, IL1-mediated polarization of CAFs toward a secretory phenotype, characterized by elaboration of IL-6, CXCL1, CXCL12, and LIF ( 11, 12 ), propagates pro-inflammatory tumor-stromal-immune crosstalk in the PDAC TME that drives therapeutic resistance ( 13 ). These tumor-permissive inflammatory CAFs (iCAF)—which co-exist in a dynamic equilibrium with other functionally divergent CAF sub-populations such as myofibroblastic CAFs (myCAFs) and antigen-presenting CAFs (apCAFs) ( 14, 15 )—beckon immunosuppressive TAMs and MDSCs to the TME, dampen anti-tumor adaptive immunity, and promote immune evasion in PDAC ( 11, 13, 16, 17 ). These underlying complexities in CAF immunobiology, coupled with the clinical failure of broad-based stromal-depleting strategies in PDAC patients ( 18, 19 ), warrant the development of more nuanced therapies to mitigate tumor-permissive inflammatory CAF programming while preserving its tumor-restraining counterparts.…”
Section: Introductionmentioning
confidence: 99%